Scientometric Analysis of Cryptography Research Output - Baskaran, C. (Journal of Information and Knowledge)
The Publication pattern, Relative Growth Rate (RGR), Doubling time (Dt), Country-wise distribution and Subject-wise papers of Cryptography published during 2000-2011 were analyzed. This bibliometric study was made using the data retrieved from the Web of Science (WoS) through the filter of the category in Cryptography as a subject search. A total number of 6610 records which were retrieved from the Web of Science was used to assess the academic productivity and distribution of research diversity of cryptography field from four major countries -China, USA, Taiwan and Japan which contributed more papers in cryptography and allied field of researches. The highest RGR is 0.44 in 2002 and Dt is 21.656 in 2008 measured during the period. China was the country with the highest productivity rare and the most-frequent partners among the collaborative papers at global level.